Doping in sport: an analysis of sanctioned UK rugby union players between 2009 and 2015 - Whitaker, L.; Backhouse, S. (Journal of Sports Sciences, 2017)
To inform anti-doping policy and practice, it is important to understand the complexities of doping. The purpose of this study was to collate and systematically examine the reasoned decisions published by UK Anti-Doping for doping sanctions in rugby union in the UK since the introduction of the 2009 World Anti-Doping Code. Case files were content analysed to extract demographic information and details relating to the anti-doping rule violation (ADRV), including individuals` explanations for how/why the ADRV occurred. Between 2009 and 2015, 49 rugby union players and one coach from across the UK were sanctioned. Over 50% of the cases involved players under the age of 25, competing at sub-elite levels. Reasons in defence of the ADRV focused on functional use and lifestyle factors rather than performance enhancement. An a priori assessment of the "need", "risk" and "consequence" of using a substance was not commonplace; further strengthening calls for increasing the reach of anti-doping education. The findings also deconstruct the view that "doped" athletes are the same. Consequently, deepening understanding of the social and cultural conditions that encourage doping remains a priority.